2008
DOI: 10.1021/ic7017709
|View full text |Cite
|
Sign up to set email alerts
|

Planar Tetracoordinate Carbon Species Involving Beryllium Substituents

Abstract: Planar tetracoordinate carbon (ptC) arrangements can be achieved by employing multiple substituents based on beryllium, despite its rather weak pi-acceptor ability. A variety of ptC-containing examples, some with more than one ptC, have been designed computationally by elaborating the planar C(BeH) 4 (2-) prototype at B3LYP/6-311++G(3df,2p) and MP2/6-311++G(3df,2p) levels of theory for some small ptC representatives. The prototype prefers a D(2h) paramagnetic triplet ground state due to Hund's rule, rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 43 publications
2
46
0
1
Order By: Relevance
“…[36] Radoms group [16] designed af amily of alkaplane molecules (for example,s pirooctaplane, 2c)w hich constrain the ptC candidate in hydrocarbon cages.A lthough approaching ap lanar C(C) 4 -type ptC more closely than ever before,s uch "mechanical" designs without "electronic" assistance must struggle to overcome the enormous strain of ap tC with a p lone-pair HOMO.More buttresses are needed to achieve planarity (for example,i nd imethanospiro[2,2]octaplane 2e). .…”
Section: Ptcs Based On the Planar Methane Dication Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[36] Radoms group [16] designed af amily of alkaplane molecules (for example,s pirooctaplane, 2c)w hich constrain the ptC candidate in hydrocarbon cages.A lthough approaching ap lanar C(C) 4 -type ptC more closely than ever before,s uch "mechanical" designs without "electronic" assistance must struggle to overcome the enormous strain of ap tC with a p lone-pair HOMO.More buttresses are needed to achieve planarity (for example,i nd imethanospiro[2,2]octaplane 2e). .…”
Section: Ptcs Based On the Planar Methane Dication Modelmentioning
confidence: 99%
“…[87a] Remarkably,e ven larger all-boron clusters, including quasiplanar structures,n amely chiral B 30 À [91] and B 35 À [92] with adouble-hexagonal vacancy ( Figure 42) as well as aplanar hexagonal B 36 À [93] (Figure 43), have been detected in the gas-phase and characterized by photoelectron spectroscopy and ab initio calculations. À,2À , [81] B 9 À , [81] B 10 ,B 11 À ,a nd B 12 [90] can be viewed as analogues of benzene on the basis of their six p electrons, because they have p-molecular orbital patterns similar to those of benzene.Aperfectly planar B 16 2À (D 2h ) [94] with 10 p electrons can be considered an all-boron naphthalene.A lso, three neutral boron clusters B 11 ,B 16 ,a nd B 17 are shown to have planar or quasi-planar structures by vibrational spectroscopy and ab initio calculations.…”
Section: Boronmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermolecular H-bridge bonds glue starbenzene pieces to- gether. Each hexagonal block in this type of flat molecules (see 1PPF 19 ) except for those on the verges links to six neighbors optimally, which arrange all the H-bridge bonds along the BeH directions and thus minimize the strain. Regardless of the size of the systems, the average bonding energy per H-bridge bond (E HBB ) remains nearly identical (see Table 3 and the Supporting Information SI3), being À33.7 (1PPF 2 ), À33.…”
Section: àmentioning
confidence: 99%
“…We recently found that the BeH group is an appropriate ligand to stabilize ptC, [19] which, along with the isolobal relationship of BeH to Li, suggested our replacing the six Li atoms in C 6 Li 6 with BeH groups. We also expected that the electron deficiency of BeH group would result in intermolecular hydrogen-bridge (H-bridge) bonds similar to that in BeH 2 dimer to meet criterion 2.…”
mentioning
confidence: 97%